1988
DOI: 10.1111/j.1432-1033.1988.tb14352.x-i2
|View full text |Cite
|
Sign up to set email alerts
|

Refolding of bacteriorhodopsin

Abstract: Staphylococcus aureus protease V8 cleaves bacteriorhodopsin to two main fragments, V-I and V-2. Proteolytic digestion of the purple membrane integrated protein is carried out in the presence of limited amounts of sodium dodecyl sulfate (0.5 g detergent/g bacteriorhodopsin). The fragment V-1 includes the arylisothiocyanate binding site (Lys41). The V-2 fragment comprises the two C-terminal transmembrane segments of bacteriorhodopsin. Improved renaturation of bacteriorhodopsin and the ternary complex, reformed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The Dumont group coexpressed fragments of Ste2p in yeast and found that these fragments reconstituted in the membrane to form a functional receptor . In vivo reconstitution has also been successful for the muscarinic M2 and M3 receptors and the dopamine D 2s receptors and in vitro reconstitution in detergent micelles was reported for the GPCR analogue bacteriorhodopsin . Based on these results many groups have been studying fragments of membrane protein receptors to better understand their structure‐function relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dumont group coexpressed fragments of Ste2p in yeast and found that these fragments reconstituted in the membrane to form a functional receptor . In vivo reconstitution has also been successful for the muscarinic M2 and M3 receptors and the dopamine D 2s receptors and in vitro reconstitution in detergent micelles was reported for the GPCR analogue bacteriorhodopsin . Based on these results many groups have been studying fragments of membrane protein receptors to better understand their structure‐function relationships.…”
Section: Introductionmentioning
confidence: 99%
“…The protein was completely denatured and then refolded into a functional protein. Initial fragment analysis was performed by digesting bacteriorhodopsin with either V8 protease or chymotrypsin, purifying the fragments and then reconstituting with complementary fragments and/or chemically synthesized fragments in micelles or H. halobium lipids . A large body of work that covered individual and multi‐TM fragments of bacterioopsin came from the Shemyakin Institute of Bioorganic Chemistry in Russia .…”
Section: Introductionmentioning
confidence: 99%